2010
DOI: 10.1177/0042098010375994
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Approaches to Measuring Food Access in Urban Areas

Abstract: GIS methods are used to construct measures of food access for neighbourhoods in the Portland, Oregon, US metropolitan area and the sensitivity of such measures to methodological variation is examined. The level of aggregation of data inputs is varied and the effect of using both Euclidean and street network distances is tested. It is found that, regardless of the level of geographical disaggregation, distance-based measures generate approximately the same conclusions about the distribution of food access in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 29 publications
5
67
2
Order By: Relevance
“…Most of the few notable exceptions have been conducted at micro levels, and tend to be related to urban facilities such as accessibility to healthcare deliveries (Langford and Higgs, 2006), dialysis service centres (Yang, 2006), urban parks (Omer, 2006) or food access (Sparks et al, 2011). These studies mainly concentrate on accessibility to certain amenities or facilities where a particular service is provided (such as a healthcare facility), or where some utility is obtained (e.g.…”
Section: Zoning Issues In Transport-related Spatial Analysis Modelsmentioning
confidence: 99%
“…Most of the few notable exceptions have been conducted at micro levels, and tend to be related to urban facilities such as accessibility to healthcare deliveries (Langford and Higgs, 2006), dialysis service centres (Yang, 2006), urban parks (Omer, 2006) or food access (Sparks et al, 2011). These studies mainly concentrate on accessibility to certain amenities or facilities where a particular service is provided (such as a healthcare facility), or where some utility is obtained (e.g.…”
Section: Zoning Issues In Transport-related Spatial Analysis Modelsmentioning
confidence: 99%
“…Such -food deserts‖ are particularly likely to be found in low-income areas, where the single mothers in this study are disproportionately located. See Sparks et al (2011) for a detailed review of research on the spatial distribution of food deserts across high-and low-income areas. 34 These controls are: log of median household income, log of population density, percent non-Hispanic white, percent foreign born, percent ages 65 and over, percent female, percent of children ages 0-2 and 3-5 living in female-headed households (all at the census tract-level), percent of children in the school eligible for free/reduced price lunch, an indicator for whether a majority of children in the school are minorities, and an indicator for whether the school receives Title I funding (all at the school-level).…”
mentioning
confidence: 99%
“…In each case, however, the various components of access were addressed separately and tradeoffs among them could not be explored. Sparks, Bania, and Leete (2011) demonstrated that the circular buffer and network service methods provide similar results. Based on a lack of differences resulting from the two methods, they concluded that researchers should use whatever method is easily accessible to them.…”
Section: Introductionmentioning
confidence: 85%
“…Most researchers have agreed that food access issues and food deserts are associated with physical places (Leete, Bania, & Sparks-Ibanga, 2012;Sparks, Bania, & Leete, 2011), despite the challenges of identifying or placing boundaries on those places. Geographical information systems (GIS) are a useful tool to measure and better understand food access and the food environment.…”
Section: Introductionmentioning
confidence: 99%